A Randomized Controlled Clinical Study to Measure the Effect of Suryanamaskar on Body Fat Percentage and Body Mass Index in Sthaulaya W.S.R. to Overweight Persons - Ravi Kumar; Durgawati Devi (Journal of Ayurveda)
Introduction:According to Charaka, Sthaulaya is a multidimensional disease, in which abnormal and excessive fat accumulation occurs in our body affecting us adversely. In 2016, the World Health Organization revealed that almost 1.9 billion adults were overweight, with over 650 million of them being obese. Despite advances in the modern medical system, the prevalence of Sthaulaya has been steadily increasing. Studies have shown that Suryanamaskar (SN) shows potential in obesity management through behavioral change, weight loss, and maintenance. In this scenario, an endeavor has been taken to see how SN affected overweight people’s body mass index (BMI) and body fat percentage (BFP).Methods:In this study, 93 cases of age group 18–50 years, having BMI ≥23 and <30 were randomly selected regardless of their race, age, sex, and socioeconomic considerations, but fully satisfied the diagnostic criteria. All the 93 participants were divided into two groups, Group A with 45 participants and Group B having 48 participants. In Group A 30-min session, 6 days/week of SN was advised while Group B was untreated control group. The total duration of the study was 2 months.Results:In Group A, SN intervention causes a statistically significant reduction in BMI and BFP scores. In untreated control Group B, a statistically insignificant reduction in BMI and BFP scores was found. In Group A, BMI and BFP scores were reduced statistically significantly as compared to the Group B participants.Conclusion:These results indicate that SN practice does have an effect on BMI and BFP in Sthaulya (overweight). Specifically, our results suggest that when Sthula (overweight) persons practice SN, their BMI and BFP decrease.